Doktrin Kelalaian Kontribusi (Contributory Negligence) Terhadap Tanggung Jawab Bank Atas Kerugian Nasabah Akibat Kesalahan Atau Kelalaian Pegawai Bank - Sadzili, Iza; Lastuti Abubakar (Jurnal Ilmiah Penegakan Hukum, 2025)
This study aims to examine in depth the application of the doctrine of contributory negligence in the context of bank legal liability for losses experienced by customers due to errors or negligence committed by bank employees. The issues raised focus on the extent to which banks can be exempted from legal liability by postulating the existence of contributory negligence from the customer, as well as the relevance of the application of this doctrine in the current legal system and banking practices in Indonesia. This study uses a normative legal approach with a literature study method and analysis of laws and regulations, especially referring to the provisions of Article 10 of the Financial Services Authority Regulation Number 22 of 2023 concerning Consumer and Community Protection in the Financial Services Sector. The results of the study show that in practice, banks as financial service business actors must still be responsible for customer losses arising from the negligence of their employees, regardless of whether or not there is a contribution of error from the customer. In addition, the doctrine of contributory negligence which is "all or nothing" is considered no longer relevant to be applied in a modern accountability system that emphasizes the principles of justice and consumer protection. Therefore, a review of the provisions that adopt the principle of contributory negligence in Indonesian banking regulations is urgent.